Evaluation and development of a novel pre-treatment method for mulberry leaves to enhance their bioactivity via enzymatic degradation of GAL-DNJ to DNJ. Issue 24 (10th November 2021) - Takasu, Soo; Parida, Isabella Supardi; Kojima, Yoshihiro; Kimura, Toshiyuki; Nakagawa, Kiyotaka
Abstract : We demonstrated the conversion of GAL-DNJ into DNJ improves mulberry leaves bioavailability and constructed a novel enzymatic-based method to induce the hydrolysis of GAL-DNJ to DNJ. Abstract : Mulberry leaves are rich in 1-deoxynojirimycin (DNJ) and 2- O -α-d -galactopyranosyl-deoxynojirimycin (GAL-DNJ). Compared to DNJ, the bioactive potency of GAL-DNJ is low. We proposed that the conversion of GAL-DNJ into DNJ may improve its bioavailability. We evaluated this hypothesis and constructed a novel enzymatic-based method to induce the hydrolysis of GAL-DNJ to DNJ in order to improve the therapeutic potency of mulberry leaves.